“You’re the boss, yo!”: Role-Play in Digital Multimodal Composition of Newcomer Youth - Michalovich, Amir (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
This case study explores how two 16-year-old newcomer youth in a Canadian secondary school navigated the digital multimodal composition process through role-play in their first digital video production at school. Employing a qualitative, case-study design, the study shows how the youth playfully accentuated collaborative over coercive power relations, as well as repositioned and represented their imagined identities as they played different assigned roles in the filmmaking process. The implications of these findings are discussed for educators and researchers considering digital multimodal composition as a classroom literacy practice.